SOSIALISASI DAN PELATIHAN PEMBUATAN E-MAGAZINE DALAM PEMBELAJARAN KIMIA @SMA NEGERI PINTAR PROVINSI RIAU [SOCIALIZATION AND TRAINING OF E-MAGAZINE MAKING IN CHEMISTRY LEARNING AT SMAN PINTAR, RIAU PROVINCE] - Tri Padila Rahmasari; Lani Dwi Kurnia; Gesty Mika Juwani; Adek Diah Murti; Khairu Anugerah P. Putra; Roza Linda (Jurnal Sinergitas PKM & CSR, 2020)
One of the problems in education is that educators have not been able to prepare innovative teaching materials in accordance with the development of science and technology. Educators are required to provide innovations to increase students’ interest in learning, especially in industrial revolution 4.0. This activity aims to provide understanding and skills to students and teachers in using electronic-based teaching materials and training of e-magazine making in chemistry learning. The activity was carried out at a public senior high school (SMAN Pintar), Riau Province, which is located in the city of Taluk Kuantan. This school is a boarding school that has a good infrastructure and facilities to support the optimization of learning science and technology in the industrial revolution 4.0. The method of implementing this program is to give a socialization about 21st century learning and the use of e-magazine as innovative teaching materials, followed by training and mentoring of teachers in making e-magazine using the Kvisoft Flipbook Maker Pro application. The results of this program are e-magazine products, usage manuals, and review books program. This activity received a positive response from students and teacher of SMAN Pintar Riau Province.Bahasa Indonesia Abstrak: Salah satu masalah dalam dunia Pendidikan adalah pendidik belum bisa menyiapkan materi ajar yang inovatif dan sesuai dengan perkembangan IPTEK. Seiring dengan tuntutan revolusi industri 4.0 yang mengedepankan IT, pendidik dituntut untuk dapat memberikan inovasi untuk meningkatkan minat belajar peserta didik. Salah satu inovasi yang bisa digalakkan adalah membuat bahan ajar berbasis IT. Kegiatan pengabdian ini bertujuan untuk memberikan pemahaman dan keterampilan kepada peserta didik dan guru dalam menggunakan bahan ajar berbasis elektronik melalui sosialisasi dan pelatihan pembuaatn e-magazine dalam pembelajaran kimia. Kegiatan pengabdian dilaksanakan di SMAN Pintar Provinsi Riau merupakan sebuah boarding school yang memiliki infrastruktur dan sarana prasaran sudah memadai sehingga diperlukan usaha pengoptimalan IPTEK agar sekolah ini bisa berperan serta dalam revolusi industri 4.0. Metode pelaksanaan pengabdian ini meliputi pemberian materi sosialisasi tentang pembelajaran abad 21, penggunaan e-magazine sebagai bahan ajar, pelatihan dan pendampingan guru dalam pembuatan e-magazine menggunakan aplikasi Kvisoft Flipbook Maker Pro. Hasil kegiatan ini berupa buku panduan program, buku tinjauan program, dan produk e-modul yang dibuat oleh tim EMBER KLASIK serta guru hasil pelatihan. E-magazine adalah modul elektronik yang memiliki tampilan seperti majalah. Kegiatan pengabdian ini memperoleh respon positif dari peserta didik dan guru SMAN Pintar Provinsi Riau.